2014
DOI: 10.1111/bjd.13099
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed‐dye laser treatment for recalcitrant viral warts: a retrospective case series of 227 patients

Abstract: 4 Sandroni P, Martin DP, Bruce BK et al. Congenital idiopathic inability to perceive pain: a new syndrome of insensitivity to pain and itch with preserved small fibers. Pain 2006; 122:210-15. 5 Weiss J, Pyrski M, Jacobi E et al. Loss-of-function mutations in sodium channel Nav1.7 cause anosmia. Nature 2011; 472:186-90. 6 Rush AM, Dib-Hajj SD, Liu S et al. A single sodium channel mutation produces hyper-or hypoexcitability in different types of neurons. Proc Natl Acad Sci USA 2006; 103:8245-50. 7 Han C, Hoeijma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
1
18
0
1
Order By: Relevance
“…Interestingly, a large retrospective study showed a high percentage of clearance of warts using high fluencies (12.5-15 J/cm²) with PDL. 5 Along with our present results, it might be hypothesiszed that the use of high fluencies could induce necrosis and is needed for optimal clearance of the warts. …”
supporting
confidence: 80%
See 2 more Smart Citations
“…Interestingly, a large retrospective study showed a high percentage of clearance of warts using high fluencies (12.5-15 J/cm²) with PDL. 5 Along with our present results, it might be hypothesiszed that the use of high fluencies could induce necrosis and is needed for optimal clearance of the warts. …”
supporting
confidence: 80%
“…3 These data infer that the quality/quantity of AT1R gene expression is correlated with psoriasis and its complications such as hypertension, heart disease and oxidative stress. [4][5][6] To confirm this notion, we studied the clinical significance of the AT1RA 1166 C receptor polymorphism and its relationship with serum concentration of lipids, oxidant/antioxidant systems and vascular adhesion protein-1(VAP-1) in 100 psoriatic patients and 100 gender-and age-matched unrelated healthy controls from west population of Iran. After informed consent, genomic DNA was extracted from the individual's peripheral blood leucocytes and AT1RA 1166 C polymorphism was detected by PCR-RFLP as previously described (Fig.…”
Section: Editormentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 227 patients, the largest number of patients with recalcitrant warts treated to date, was recently published by Sparreboom et al. . The clearance rate, including the one‐year follow‐up period, ultimately came to a total of 86 %.…”
Section: Cutaneous Wartsmentioning
confidence: 99%
“…Die bislang größte behandelte Patientenzahl mit therapieresistenten Verrucae von insgesamt 227 Patienten wurde kürzlich von Sparreboom et al. beschrieben . Am Ende zeigte sich eine Abheilung, auch im Nachbeobachtungszeitraum von einem Jahr, von insgesamt 86 %.…”
Section: Kutane Verrucaeunclassified